(3UhQI GdESdGe h GdeSdejf aj hSGFd GdEYdGe GdLOjOI (B/s - (3aQjOI(B,(3adGc (B;(3LaGadIs ((3GdLRGFQ (B:s (3jhJhHjG ddfTQ h GdJhRjY ,s, 2021)
(3jSJYQV gPG GdcJGH UhQI GdGSdGe h GdeSdejf aj GdZQH h YHQ GdMbH GdRefjI GdeNJdaI dfab YfO Cge GdYhGed GdJj SGgeJ aj JTcjd gPg GdUhQI dOi GdZQH h dfYQL HYOgG Ydi XGgQI GdESdGehahejG fHMK CSHGHgG h eXGgQgG h GfYcSGJgG Ydi GdGSdGe h GdeSdejf h GdYGdejf GdYQHj h GdGSdGej Ke fJWdQb dgLeGJ (B11(3SHJeHQ (B2001 (3h OhQgG aj JfGej XGgQI GdNha ef GdGSdGe h MedGJ GdJThjg GdZQHjI GdJj WGdJ gPG GdCNjQ HYO gPg GdgLeGJ dfHMK HYOgG HYV GdMQcGJ GdefGhFI ddGSdGe aj GdZQH h Gdhbha Ydi ChLg efGgVJgG ddGSdGe h GdeSdejf ef OhGNdfG ef NdGd OQGSI HYV GdJfXjeGJ GdLgGOjI h GdGQgGHjI GdJj TcdJ GdhLg GdBNQ ddJThjg(B.s
Keywords: (3GdESdGes; (3GdeSdejfs